Research on performance of a hydrogen/n-butanol rotary engine at idling and varied excess air ratios. (15th April 2018) - Su, Teng; Ji, Changwei; Wang, Shuofeng; Cong, Xiaoyu; Shi, Lei
Highlights: Idle performance of a H2 / n -butanol rotary engine at lean was studied. Engine instability and fuel consumption were reduced after blending H2 . Combustion duration was decreased by H2 addition. HC and CO emissions were dropped with H2 enrichment. Abstract: The structure chamber of rotary engine is irregular compared with traditional reciprocating engines. Pure n -butanol rotary engine normally encounters partial burning and even misfire at idling and lean conditions. Comparatively, hydrogen supplement can ameliorate performance of original engine. In this paper, experimentation of a rotary engine fueled with pure n -butanol and hydrogen/ n -butanol blends at idling and different excess air ratios was conducted. Experimental results manifested that hydrogen addition effectively decreased the engine instability and fuel energy flow rate. To be specific, fuel energy flow rate at the excess air ratio of 1.05 was reduced from 23.63 MJ/h to 21.26 MJ/h when 3% hydrogen was added. Combustion duration was lowered after introducing hydrogen. Maximum chamber temperature was heightened after hydrogen addition. HC and CO emissions were reduced when 3% hydrogen was added. NOx emissions were reduced when the mixture was leaned out.